PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2017-2020 - Napiajo Napiajo; Syarif Ahmadin; Lia Nurina (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2022)
Dividend Policy concerns the issue of the use of profits which are the rights of shareholders, the profits can be divided as dividends or retained for reinvestment. This study aims to analyze the Effect of Liquidity and Leverage on Dividend Policy in food and beverage companies listed on the Indonesia Stock Exchange. 2017-2020. The population of this study is all food and beverage companies listed on the Indonesia Stock Exchange 2017-2020, as many as 33 companies. The sampling method used is purposive sampling with a sample of 13 companies. This study uses the associative method, multiple linear regression analysis techniques and partial test (t), but before testing the hypothesis, the classical assumption test is carried out first. The results of this study indicate that, Liquidity (Current Ratio), Leverage (Debt to Equity Ratio) simultaneously has no significant effect on Dividend Policy (Dividend Payout Ratio). Partially Liquidity (Current Ratio) has a positive effect on Dividend Policy (Dividend Payout Ratio), Leverage (Debt to Equity Ratio) has no effect on Dividend Policy (Dividend Payout Ratio).